The Protective Effect of Naringin against Bleomycin-Induced Pulmonary Fibrosis in Wistar Rats - Turgut, Nergiz H.; Kara, Haki; Elagoz, Sahende; Deveci, Koksal; Gungor, Huseyin; Arslanbas, Emre (Pulmonary Medicine, 2016)
The aim of the current study was to investigate the protective effect of naringin on bleomycin-induced pulmonary fibrosis in rats. Twenty-four Wistar rats randomly divided into four groups (control, bleomycin alone, bleomycin + naringin 40, and bleomycin + naringin 80) were used. Rats were administered a single dose of bleomycin (5 mg/kg; via the tracheal cannula) alone or followed by either naringin 40 mg/kg (orally) or naringin 80 mg/kg (orally) or water (1 mL, orally) for 14 days. Rats and lung tissue were weighed to determine the lung index. TNF-α and IL-1β levels, hydroxyproline content, and malondialdehyde (MDA) levels were assayed. Glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) activities were determined. Tissue sections were stained with hematoxylin-eosin, Masson’s trichrome, and 0.1% toluidine blue. TNF-α, IL-1β, and MDA levels and hydroxyproline content significantly increased (p<0.01) and GPx and SOD activities significantly decreased in bleomycin group (p<0.01). Naringin at a dose of 80 mg/kg body weight significantly decreased TNF-α and IL-1β activity, hydroxyproline content, and MDA level (p<0.01) and increased GPx and SOD activities (p<0.05). Histological evidence supported the results. These results show that naringin has the potential of reducing the toxic effects of bleomycin and may provide supportive therapy for conventional treatment methods for idiopathic pulmonary fibrosis.